2020
DOI: 10.3390/nu12113486
|View full text |Cite
|
Sign up to set email alerts
|

Whole Goat Milk as a Source of Fat and Milk Fat Globule Membrane in Infant Formula

Abstract: Cow milk is the most common dairy milk and has been extensively researched for its functional, technological and nutritional properties for a wide range of products. One such product category is infant formula, which is the most suitable alternative to feed infants, when breastfeeding is not possible. Most infant formulas are based on cow milk protein ingredients. For several reasons, consumers now seek alternatives such as goat milk, which has increasingly been used to manufacture infant, follow-on and young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 105 publications
(272 reference statements)
0
45
0
2
Order By: Relevance
“…The low levels of oleic, linoleic acid, and α‐linolenic acid and only trace amounts of docosahexaenoic or arachidonic acid in milk fat mean that formulas must have an additional source of these fatty acids, predominantly from vegetable oils (Delplanque, Gibson, Koletzko, Lapillonne, & Strandvik, 2015; Wei, Jin, & Wang, 2019). Although a formula made with goat milk can use vegetable oils only (Maduko & Park, 2007), it is also possible to use a mixture of goat milk fat and vegetable oils to meet the required fatty acid profiles when formula is made from whole goat milk (Gallier, Tolenaars, & Prosser, 2020; Prosser et al., 2010). Including milk fat reduces exposure of the infant to phytosterols (Claumarchirant, Matencio, Sanchez‐Siles, Alegría, & Lagarda, 2015), while retaining milk fat globule membrane components that are lacking in vegetable oils (Gallier et al., 2020; Hageman, Danielsen, Nieuwenhuizen, Feitsma, & Dalsgaard, 2019; Heird, 2007).…”
Section: Studies Of Infant Formulamentioning
confidence: 99%
“…The low levels of oleic, linoleic acid, and α‐linolenic acid and only trace amounts of docosahexaenoic or arachidonic acid in milk fat mean that formulas must have an additional source of these fatty acids, predominantly from vegetable oils (Delplanque, Gibson, Koletzko, Lapillonne, & Strandvik, 2015; Wei, Jin, & Wang, 2019). Although a formula made with goat milk can use vegetable oils only (Maduko & Park, 2007), it is also possible to use a mixture of goat milk fat and vegetable oils to meet the required fatty acid profiles when formula is made from whole goat milk (Gallier, Tolenaars, & Prosser, 2020; Prosser et al., 2010). Including milk fat reduces exposure of the infant to phytosterols (Claumarchirant, Matencio, Sanchez‐Siles, Alegría, & Lagarda, 2015), while retaining milk fat globule membrane components that are lacking in vegetable oils (Gallier et al., 2020; Hageman, Danielsen, Nieuwenhuizen, Feitsma, & Dalsgaard, 2019; Heird, 2007).…”
Section: Studies Of Infant Formulamentioning
confidence: 99%
“…In addition, there are infant formulas, including formulas with bovine cream or anhydrous milk fat and whole goat milk formulas, that contain milk fat blended with vegetable oils to provide total and sn -2 palmitic acid without the use of palm oil or structured triglycerides. 46,77 Manios et al 78 found that infants fed a formula with up to 50% of its lipids as milk fat had lower excretion of palmitate soaps, total fatty acid soaps and calcium compared to infants fed a control vegetable oil-based formula.…”
Section: Composition Of Human Milk and Different Infant Formulasmentioning
confidence: 99%
“…The utilization of whole goat milk as the sole protein source in infant formulas maximizes the level of fat, milk fat globule membrane, sn-2 palmitic acid, and medium and short chain fatty acids. These characteristics enhance the microstructure and composition of whole goat milk-based infant formula, emulating the complex fat globules seen in human milk fat, and have been demonstrated to aid digestion, as well as cognitive and immunological development ( 132 ). Goat milk, particularly in developing nations, is a viable dairy alternative for meeting the nutritional needs of children, infants, and adults ( 1 ).…”
Section: Health Benefitsmentioning
confidence: 99%